Impact force and occurrence condition of geyser boiling in two-phase closed thermosyphon - Seo, Jin Hyeuk; Lee, Jungchul; Lee, Jungho (International Communications in Heat and Mass Transfer, 2024)
The Geyser boiling phenomenon (GBP) is unstable behavior inside a two-phase closed thermosyphon (TPCT). The mechanism of GBP occurrence is still not clearly understood. Therefore, understanding GBP is not just an academic pursuit but is essential for designing the TPCT. Based on the visualization, the GBP was defined, and a novel experiment with synchronized measurement among temperature, pressure, and force analyzed the mechanism of GBP. Experiments were taken to understand GBP by varying filling ratios (50 %, 75 %, and 100 %) of working fluid and heat fluxes. The results showed that a sufficient liquid layer at the top of the bubble is required for GBP to occur and that the bubble growth rate affects the thickness of the liquid layer. When GBP occurred, the average force was at least 0.5 N, but in some cases, an average force of 1 N or more appeared under the condition that GBP did not occur. When the frequency of the force was high, even a small average force could make a significant cumulative force. This study provides valuable information for numerical analysis based on the quantitative forces measured by the load cell, opening a new perspective on the safety and reliability of TPCTs.
Keywords: Average force; Filling ratio; Force conditions; Geyse boiling phenomenon; Impact force; Liquid layer; Occurrence conditions; Two-phase closed thermosiphon; Two-phase closed thermosyphon; Unstable behavior; Filling ratio; Geyser boiling phenomena (GBP); Heat flux; Impact force; Two-phase closed thermosyphon (TPCT)